The Ivory Saltcellars: A contribution to the history of Islamic expansion in Greater Senegambia during the 16th and 17th centuries - Thiago H. Mota (Afriques)
This article aims to discuss Islamic expansion in West Africa during the 16th and 17th centuries along with carved ivory production. The analysis concerns the Greater Senegambia, a region comprised of the Senegal River basin in the north, the Futa Jalon plateau in the east, and northern Sierra Leone in the south. The study is based on European written sources, African oral traditions, and African carved ivories owned by the Ethnologisches Museum in Berlin, Germany. Its main hypothesis is that the 16th and 17th centuries comprised the moment of Islamic social expansion, before Islam turned into a major political force in Senegambia during the 18th and 19th centuries. Therefore, this paper’s goal is to present a conjoint understanding of the ivory pieces and early Islamic expansion, by focusing on the images carved in ivory saltcellars that are associated with Western African Islamic written culture.